Person-Organization's Environment Fit and it's Reflection on the Work Outcomes - الملا, عبد الرحمن مصطفى; ابراهيم, مها فاضل (Journal of Economics and Administrative Sciences, 2016)
This study aims to studying of Person and organization’s environment fit in a sample of Private bank’s reflection in its basic dimensions (Person-organization fit ,Person-Job fit, Person-group fit and Person- Person-fit )in the Work Outcomes (job satisfaction, the intention to leave the job, Job Engagement, and organizational  citizenship behavior ).The questionnair’e has been used as a basic  instrument to gather data , As well as personal interviews with some of the staff of the research sample of private banks which were represented by (5) and included banks (Bank of Assyria for investment, the North Bank for Finance and Investment , Bank of the Tigris and Euphrates Islamic, Al-Mansour Bank for Investment )that the sample contains (103) individuals who occupy the post of branch manager or a department head or an employee, and that data has been processed by using the statistic Package (SPSS ).The most important conclusions of the present study is that the Person-organization  environment fit enables the studied organization to use it in solving its problems ,and the results showed that the achieving of high levels of Person-organization environment fit has been described as one of the basic element in maintaining of manpower necessary to confront the competitive challenges ,that the relation and interaction between the individual and organizational environment result in behaviors that assist the organization in achieving the common objectives for both of them, as well as there is a strong significant correlation between Person-organization’s environment fit and the Work Outcomes .The re commendation’s focused on the maximum benefit from functioning the dimensions of Person-organization’s environment in a balanced way for the individual to increase their perception of the value of their work and their sense with progress and success, and this task is achieved by the attention paid by the bank management to it’s employees and to notify the employees with the result of their work , in addition to the importance of giving enough opportunities to it’s individuals by solving the problems that obstruct their work, and the attempt of benefiting from the dimensions of Person-organization environment fit in influencing in Work outcomes by joining the individuals with the courses or programs of social adaptation to narrow the gap between the Person and organizations environment in away that achieves good level of Person-organizations environment to increase the Work outcomes and their productivit .